The putative roles of FSH and AMH in the regulation of oocyte developmental competence: from fertility prognosis to mechanisms underlying age-related subfertility - Buratini, Jose [UNESP]; Dellaqua, Thaisy Tino [UNESP]; Dal Canto, Mariabeatrice; La Marca, Antonio; Carone, Domenico; Mignini Renzini, Mario; Webb, Robert (Oxford University Press (OUP), 2022)
BACKGROUND: Fertility loss during female ageing is associated with increasing basal FSH and decreasing anti-Müllerian hormone (AMH) concentrations, together with compromised oocyte quality, presumably due to increased oxidative stress (OS) and DNA damage, as well as reduced metabolic and meiotic competences. Basal FSH and AMH circulatory concentrations have been broadly utilized as IVF success predictors, regardless of fluctuations in prognostic accuracy; basal FSH and AMH perform better in pre-advanced maternal age (AMA: >35 years) and AMA patients, respectively. The relationships between FSH and AMH intrafollicular levels and IVF outcomes suggest, nevertheless, that both hormones regulate oocyte competence, supporting the hypothesis that changes in FSH/AMH levels cause, at least in part, oocyte quality degradation during ageing. To understand the reasons behind the fluctuations in FSH and AMH prognostic accuracies and to clarify their participation in mechanisms determining oocyte competence and age-related subfertility, a deeper knowledge of the regulation of FSH and AMH intrafollicular signalling during the female reproductive lifespan, and of their effects on the cumulus-oocyte complex, is required. OBJECTIVE AND RATIONALE: An extensive body of information on the regulation of FSH and AMH intrafollicular availability and signalling, as well as on the control of folliculogenesis and oocyte metabolism, has been accumulated. However, these datasets have been explored within the relatively narrow boundaries of their specific subjects. Given the aforementioned gaps in knowledge and their clinical relevance, herein we integrate clinical and basic data, within a wide biological perspective, aiming to shed light on (i) the reasons for the variability in the accuracy of serum FSH and AMH as fertility markers, and on (ii) the potential roles of these hormones in mechanisms regulating oocyte quality, particularly those associated with ageing. SEARCH METHODS: The PubMed database encompassing the period between 1960 and 2021 was searched. Principal search terms were FSH, FSH receptor, AMH, oocyte, maternal age, cumulus, transzonal projections (TZPs), actin, OS, redox, reactive oxygen species, mitochondria, DNA damage, DNA repair, aneuploidy, spindle, meiosis, gene expression, transcription, translation, oocyte secreted factors (OSFs), cAMP, cyclic guanosine monophosphate, natriuretic peptide C, growth differentiation factor 9, bone morphogenetic protein 15 and fibroblast growth factor. OUTCOMES: Our analysis suggests that variations in the accuracy of fertility prognosis reflect a modest association between circulatory AMH levels and oocyte quality as well as increasing basal FSH inter-cycle variability with age. In addition, the basic and clinical data articulated herein support the hypothesis that increased intrafollicular FSH levels, as maternal age advances, may override the physiological protective influences of AMH and OSFs against excessive FSH signalling in cumulus cells. This would result in the disruption of oocyte homeostasis via reduced TZP-mediated transfer of cumulus-derived molecules essential for meiotic competence, gene expression, redox activity and DNA repair. WIDER IMPLICATIONS: In-depth data analysis, encompassing a wide biological perspective has revealed potential causative mechanisms of age-related subfertility triggered by alterations in FSH/AMH signalling during the female reproductive life. Insights from new mechanistic models arising from this analysis should contribute to advancing our comprehension of oocyte biology in humans and serve as a valuable reference for novel AMA subfertility treatments aimed at improving oocyte quality through the modulation of AMH/FSH action.
Keywords: AMH; cumulus cells; fertility prognosis; FSH; maternal age; oocyte; transzonal projections